3-- 2-- 1-- liftoff! an educator's guide with activities in science, mathematics, technology, and language arts. - United States. National Aeronautics and Space Administration; Lyndon B. Johnson Space Center (Houston, Tex. : National Aeronautics and Space Administration, NASA Johnson Space Center, 2002)
Explains the International Space Station and the role rockets play in its construction.
Shipping list no.: 2004-0095-M.
"EG-2002-02-001-JSC."
Distributed to depository libraries on microfiche.
Includes bibliographical references (p. 89-90).
Gr. K-4.
Also available via Internet from the NASA web site. Address as of 2/19/04: http://spacelink.nasa.gov/Instructional.Materials/NASA.Educational.Products/3-2-1.Liftoff/3.2.1.Liftoff.pdf; current access is available via PURL.
Keywords: Aeronautics -- Study and teaching (Primary)